Evaluation of Curvularia lunata Strain B6 as a Potential Mycoherbicide to Control Barnydrgrass (Echinochloa crus-galli) - Jing LI; Tao WEI; Ai-rui SUN; Han-wen NI (Journal of Integrative Agriculture)
The virulent strain B6 of Curvularia lunata was screened out from 65 fungus strains isolated from the diseased leaves of barnyardgrass (Echinochloa crus-galli). Greenhouse and field studies were conducted to evaluate the feasibility of the strain being exploited as a mycoherbicide for barnyardgrass control in paddy fields. The results of pathogenicity experiments showed that this strain was highly pathogenic to barnyardgrass at the 1- to 2.5-leaf stages. The fresh weight reduction increased with the increase of inoculated conidial concentrations and the prolongation of dew duration. Strain B6 provided excellent barnyardgrass control when it was applied at the concentration of 1×104-1×106 conidia mL−1 in paddy fields with water layer. This strain was very safe to rice and the most plant species except wheat, barley and corn. Findings of this study indicated that this strain could be a potential mycoherbicide for barnyardgrass control in paddy fields in the future.